Experimental evaluation of tertiary blends of water in diesel with butyl alcohol using compression ignition engine - M. K., Akasyah; I. M., Yusri; R., Mamat; M. F., Jamlos; A. P. P., Abdul Majeed (IOP Publishing, 2021)
Alcohols are important alternative fuel resources for diesel engines. Prominent fuels of the three types include water in diesel reduce engine temperature and NOx and alcohols with a high number of carbons. There is potential to use tertiary blends of diesel fuel, water and higher alcohols, such as butanol, in diesel engines for the purpose of increasing the use of alternative fuel and decreasing fossil fuel consumption. In this study, diesel fuel (D) was mixed with water (5%), and butanol (5% - 10%). Test fuel blends of W5DBu5 (5% of water, 5% of butanol), W5DBu10 (5% of water, 10% of butanol) and W5DBu15 (5% of water, 15% of butanol) were prepared using ultrasonic emulsifier and tested in a diesel engine. It carried engine performance and exhaust emission tests of the blends out on a four-cylinder, four-cycle diesel engine generator at a fixed load of 50% and various engine speeds from 1000 rpm to 3000 rpm. According to engine test results, brake specific fuel consumptions (BSFC) of Blended fuels decrease compared to diesel at all engine speed. As compared to diesel, W5DBu15 presented the best oxides of nitrogen (NOx) at a speed of 2000 rpm with a reduction of 34.7%.